2011
DOI: 10.1016/j.ijsu.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

DRUJ instability after distal radius fracture: A comparison between cases with and without ulnar styloid fracture

Abstract: Our study demonstrated that untreated stable or minimally displaced ulnar styloid fracture accompanied by distal radius fracture, has no adverse effect on DRUJ stability following ORIF of the radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
0
31
0
3
Order By: Relevance
“…14,15,29,33 Similarly, we found that the wrist immobilization period for sugar-tong splinting ranged from 4 to 9 weeks. It is likely that these wide variations in immobilization period during conservative treatment are due to different levels of blood supply and TFCC injury.…”
Section: Table 5 Three-month Follow-up Outcomesmentioning
confidence: 62%
See 2 more Smart Citations
“…14,15,29,33 Similarly, we found that the wrist immobilization period for sugar-tong splinting ranged from 4 to 9 weeks. It is likely that these wide variations in immobilization period during conservative treatment are due to different levels of blood supply and TFCC injury.…”
Section: Table 5 Three-month Follow-up Outcomesmentioning
confidence: 62%
“…Furthermore, they did not compare and analyze the outcomes for the various treatments, based on the presence/absence and type of ulnar styloid process fracture in patients with DRUJ instability. 8,10,13,15 Furthermore, none of the studies were prospective, or had a follow-up period of 1 year or longer. Therefore, we used a prospective design with an extended follow-up to analyze outcomes according to the presence/absence and type of ulnar styloid process fracture, in patients with acute DRUJ instability accompanying distal radius fracture.…”
Section: Table 5 Three-month Follow-up Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kazemian et al 20 used external fixation to treat DRF with USF, proving that USF does not influence DRUJ instability. Furthermore, Lindau et al 21 reported that DRUJ problem after DRF has poor prognosis, but its instability was not correlated with the presence of USF.…”
Section: Discussionmentioning
confidence: 99%
“…Neoperativno liječenje podrazumijeva imobilizaciju udlagama i mirovanje podlaktice, često i lakta (6,7). Ipak ima prijeloma koji uvijek zahtijevaju operacijsko liječenje, dug oporavak i neizvjesnog su ishoda (8,9). Tako ozljede u području ploče rasta, bez obzira na ispravno provedeno liječenje, mogu ostaviti trajne posljedice.…”
Section: Uvodunclassified